Parental Self-Efficacy in Helping Children Succeed in School Favors Math Achievement - Liu, Ye; Leighton, Jacqueline P. (Frontiers in Education, 2021)
Parents play an important role in children’s academic achievement. The purpose of the present study was to explore the internal structure of an established parent survey and to investigate the relationships among different aspects of parental involvement in predicting children’s mathematics achievement. The study involved secondary data from 139 parents and math achievement scores of 121 elementary school-aged children. Guided by Hoover-Dempsey and Sheldon’s (2005) Revised Parent Involvement Process model, a Principal Component Analysis with direct oblimin rotation was conducted on the parent survey, followed by path analysis to predict children’s math achievement. Five principal components were retained. Standardized results of the path analysis indicated that parental self-efficacy had the largest direct effect on children’s math achievement. Moreover, parental self-efficacy was favoured directly by parental perceptions of specific school invitations to become involved. These findings shed light on the interplay between parental involvement and children’s achievement and underscore the importance of school-family collaboration, which can potentially link to parental self-efficacy.